Hypothalamic miR-30 regulates puberty onset via repression of the puberty-suppressing factor, Mkrn3 - Violeta Heras; Susana Sangiao-Alvarellos; Maria Manfredi-Lozano; María J. Sanchez-Tapia; Francisco Ruiz-Pino; Juan Roa; Maribel Lara-Chica; Rosario Morrugares-Carmona; Nathalie Jouy; Ana P. Abreu; Vincent Prevot; Denise Belsham; et al. (PUBLIC LIBRARY SCIENCE, 2022)
Mkrn3, the maternally imprinted gene encoding the makorin RING-finger protein-3, has recently emerged as putative pubertal repressor, as evidenced by central precocity caused by MKRN3 mutations in humans; yet, the molecular underpinnings of this key regulatory action remain largely unexplored. We report herein that the microRNA, miR-30, with three binding sites in a highly conserved region of its 3 ' UTR, operates as repressor of Mkrn3 to control pubertal onset. Hypothalamic miR-30b expression increased, while Mkrn3 mRNA and protein content decreased, during rat postnatal maturation. Neonatal estrogen exposure, causing pubertal alterations, enhanced hypothalamic Mkrn3 and suppressed miR-30b expression in female rats. Functional in vitro analyses demonstrated a strong repressive action of miR-30b on Mkrn3 3 ' UTR. Moreover, central infusion during the juvenile period of target site blockers, tailored to prevent miR-30 binding to Mkrn3 3 ' UTR, reversed the prepubertal down-regulation of hypothalamic Mkrn3 protein and delayed female puberty. Collectively, our data unveil a novel hypothalamic miRNA pathway, involving miR-30, with a prominent role in the control of puberty via Mkrn3 repression. These findings expand our current understanding of the molecular basis of puberty and its disease states.